2018
DOI: 10.3846/jbem.2018.5536
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Residents’ Perceptions, Attitudes and Behavioral Intention Toward Festivals and Special Events: A Pre-Event Perspective

Abstract: This article reports the results of research investigating residents’ perceptions, attitudes and behavioral intention (BI) toward sports festivals and special events (FSE) from a pre-event perspective. A structural equation modeling (SEM) was utilized. Two sets of theoretical frameworks have been employed for this study: Social Exchange Theory (SET) and Social Representation Theory (SRT). A quantitative analysis was utilized. Using structural equation modeling (SEM). The authors have identified a strong associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Moscovici (1983, p. 122) defined social representations as systems of preconceptions, images and values with their own cultural meaning independent of personal experience. SRT proposes the collective concept of values, beliefs, cultures, symbols and traditions commonly held by members within a society (Li et al, 2018). Group consensus can form individual perceptions, and gradually guide and control individual behavior (Becken, 2016).…”
Section: Social Representation Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…Moscovici (1983, p. 122) defined social representations as systems of preconceptions, images and values with their own cultural meaning independent of personal experience. SRT proposes the collective concept of values, beliefs, cultures, symbols and traditions commonly held by members within a society (Li et al, 2018). Group consensus can form individual perceptions, and gradually guide and control individual behavior (Becken, 2016).…”
Section: Social Representation Theorymentioning
confidence: 99%
“…Tourists establish their perceptions of the event through their direct experience of the event activities which is more directly controlled by the individual than other factors (Li et al, 2018;Ying, 2004;Rai and Nayak, 2020). However, when tourists have limited information from their direct experience of an event, other sources of social representation become more salient.…”
Section: Social Representation Theory and Event Imagementioning
confidence: 99%
See 2 more Smart Citations
“…Li, Hsu, & Lawton [35] found that Shanghai residents' perception changes throughout the Expo 2010 full life cycle and the residents' perceived impacts at the community level were more positive than at the individual level. Role of media and marketing campaigns to promote the social and economic implications of the event and also to explore opportunities through which the residents could be involved in the whole process of planning and implementation, has been highlighted in the previous studies [36]. In contrast to the findings of many studies establishing a positive relationship between willingness to host the event and residents' perception of economic impacts, Balduck, Maes & Buelens [37] found that the more residents believed the event generates economic and tourism development, the less willing they were to host the event next year.…”
Section: Theoretical Framework and Conceptualizationmentioning
confidence: 99%